2018
DOI: 10.1007/s12035-018-1119-4
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Amnesia Is Related to Developmental Immaturity of the Maintenance Mechanisms for Long-Term Potentiation

Abstract: Infantile amnesia (IA) refers to the inability of adults to recall episodic memories from infancy or early childhood. While several hypotheses have been proposed to explain the occurrence of IA, the neurobiological and molecular bases for this accelerated forgetting phenomenon remain elusive. Using hippocampus-dependent object-location memory and contextual fear conditioning tasks, we confirmed that infant mice trained at postnatal day 20 (P20) displayed deficits in long-term memory retention compared to adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Hippocampal cannula implantation and drug injection. Mice were bilaterally implanted under deep pentobarbital (50 mg/kg, i.p., supplemented as required) anesthesia with 28 gauge guide cannulas (Plastics One) in the dorsal hippocampus as previously described (Tsai et al, 2019). Coordinates for mice were À2.3 mm posterior to bregma, 61.5 mm bilateral to midline, and 1.8 mm ventral to brain surface according to adult mouse brain stereotaxic atlas (Franklin and Paxinos, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal cannula implantation and drug injection. Mice were bilaterally implanted under deep pentobarbital (50 mg/kg, i.p., supplemented as required) anesthesia with 28 gauge guide cannulas (Plastics One) in the dorsal hippocampus as previously described (Tsai et al, 2019). Coordinates for mice were À2.3 mm posterior to bregma, 61.5 mm bilateral to midline, and 1.8 mm ventral to brain surface according to adult mouse brain stereotaxic atlas (Franklin and Paxinos, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to LTP reversal deficiency in juvenile mice, juvenile animals learn faster than adult animals. A recent report showed by using hippocampus-dependent object-location memory and contextual fear conditioning tasks confirmed that juvenile mice displayed deficits in long-term memory retention compared with adult mice (Tsai et al, 2018), which was probably because juvenile mice have insufficient memory encoding (Ge et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The cellular, molecular, and electrophysiological constraints of infantile amnesia are not fully known. Prior to P21, LTP is more difficult to induce (Blair et al, 2013; Dumas, 2012) and dissipates more rapidly (Harris & Teyler, 1984; Tsai, Huang, & Hsu, 2019; Yasuda, Barth, Stellwagen, & Malenka, 2003). It is possible that after IA training at this age, the context‐shock association is encoded through a developmental form of “fragile” LTP, which could support memory retrieval at short time periods following behavior training (Travaglia et al, 2016).…”
Section: Nonionotropic Nmdar Signaling In Vivo May Act To Limit Information Processing and Repress Retrievable Spatial Memory Prior To Pomentioning
confidence: 99%